Can Cycle Threshold Value of RT-PCR for SARS-CoV-2 Predict Secondary Bacterial Infections in Patients with Coronavirus Disease? - Sharma, Supriya; Regmi, Sushma; Sapkota, Rajendra; Aryal, Shreedhar; Sharma Chalise, Bimal; Gurung, Krishna; Thapa, Jiwan; Adhikari, Sanjib; Sharma, Suprina; Poudel, Pramod; et al. (Tribhuvan University Journal of Microbiology, 2024)
Objectives: This study aims to investigate the relationship between cycle threshold (Ct) values of RT-PCR for SARS-CoV-2, as a marker of viral load, and the occurrence of secondary bacterial infections in hospitalized COVID-19 patients. Methods: A cross-sectional study was conducted among 141 COVID-19 patients at Sukraraj Tropical and Infectious Disease Hospital, Nepal, between July 2022 and June 2023. Bacterial cultures were performed for hospitalized patients. Ct values for SARS-CoV-2 N and Orf 1ab genes were compared between patients with and without secondary bacterial infections. Results: Out of 32 hospitalized patients, 11 (34.37%) had secondary bacterial infections. The median Ct values of the N gene were slightly lower in patients with secondary bacterial infections (19.5) compared to those without (19.0), though this difference was not statistically significant (p = 0.2113). Similar trends were observed for the Orf1ab gene (20.5 vs. 19.5; p = 0.3125). The most frequently isolated bacterial pathogen was Klebsiella pneumoniae, while Acinetobacter baumanii and E. coli were associated with the lowest Ct values. Conclusion: While patients with secondary bacterial infections tended to have lower Ct values, no statistically significant relationship was observed between Ct values and the occurrence of secondary bacterial infections. However, Ct values might still provide supplementary insights into disease severity and the risk of secondary infections.